2016
DOI: 10.1016/j.oceaneng.2016.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic performance evaluation of a tidal turbine with leading-edge tubercles

Abstract: This paper contributes to the investigations into the feasibility of improving the performance of a marine current turbine using a biomimetic concept inspired from the leading-edge tubercles on the flippers of humpback whales. An experimental test campaign was recently conducted in the Emerson Cavitation Tunnel at Newcastle University and details of this test campaign together with the findings are summarised in the paper A set of tidal turbines with different leading-edge profiles was manufactured and tested to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…Under the above circumstances, continuing the design and optimisation work on tidal turbine blades started by Wang et al (2007), the team in the Emerson Cavitation Tunnel (ECT), Newcastle University has recently initiated a new turbine blade study, by applying the leadingedge tubercles of humpback whale flippers to a tidal turbine (Shi et al, 2016a;Shi et al, 2016b). The tubercles have the potential to improve the performance of foils.…”
Section: Introductionmentioning
confidence: 99%
“…Under the above circumstances, continuing the design and optimisation work on tidal turbine blades started by Wang et al (2007), the team in the Emerson Cavitation Tunnel (ECT), Newcastle University has recently initiated a new turbine blade study, by applying the leadingedge tubercles of humpback whale flippers to a tidal turbine (Shi et al, 2016a;Shi et al, 2016b). The tubercles have the potential to improve the performance of foils.…”
Section: Introductionmentioning
confidence: 99%
“…The biomimetic tubercles produce a higher induction factor, hence a lower velocity in the wake field, which result in higher power and thrust coefficients. A higher power was also measured in [16] at lower Tip Speed Ratios (TSRs), with respect to a tidal turbine with no tubercles. [14] It was also observed that the tubercles improve the starting performance of the device, by reducing the cut-in velocity.…”
Section: Applicationsmentioning
confidence: 97%
“…This was also confirmed by Shi et al [12], who also found that tubercled tidal turbine blades underwent cavitation earlier, but the misty type cloud cavitation was confined to the areas between the tubercles. The effect of leading edge tubercles on the performance of tidal turbine blades was extensively studied by several researchers, as in [12][13][14][15][16][17] . Grueber et al [17] carried out towing tank tests on a set of tidal [17] turbine blades, in order to quantify the effect of leading edge tubercles on the performance.…”
Section: Applicationsmentioning
confidence: 99%
“…They will not be repeated once again in this paper in order to keep a concise context. In addition to these conventional blade design methods that were developed based on the fundamental theory of hydro-and aero-dynamics, the boom of designing efficient blade using biomimetic methods is also seen in recent years [11][12][13][14][15][16]. Biomimetic techniques take inspiration from natural designs.…”
Section: Introductionmentioning
confidence: 99%
“…A classic example is the humpback whale turbine blades, which adapt the whale's flipper and the flipper leading-edge tubercles to the design of blades [11,12]. Moreover, the positive contribution of the leading-edge tubercles to improving the energy capture efficiency of the blade has been validated in many numerical and experimental researches [13][14][15]. However, leading-edge tubercles can be made on the blade only in manufacturing process.…”
Section: Introductionmentioning
confidence: 99%